Download presentation

Presentation is loading. Please wait.

Published byJennifer Fletcher Modified over 6 years ago

1
**Warm up: Solve using a method of your choice.**

x − 2y = 11 2x + 2y = 19

2
**solve systems of equations using elimination with multiplication.**

Objective You will be able to: solve systems of equations using elimination with multiplication.

3
**Solving Systems of Equations**

So far, we have solved systems using graphing, substitution, and elimination. These notes go one step further and show how to use ELIMINATION with multiplication. What happens when the coefficients are not the same? We multiply the equations to make them the same! You’ll see…

4
**Solving a system of equations by elimination using multiplication.**

Step 1: Put the equations in Standard Form. Standard Form: Ax + By = C Step 2: Determine which variable to eliminate. Look for variables that have the same coefficient. Step 3: Multiply the equations and solve. Solve for the variable. Step 4: Plug back in to find the other variable. Substitute the value of the variable into the equation. Step 5: Check your solution. Substitute your ordered pair into BOTH equations.

5
Example 1 2x + 2y = 6 3x – y = 5 Step 1: Put the equations in Standard Form. They already are! None of the coefficients are the same! Find the least common multiple of each variable. LCM = 6x, LCM = 2y Which is easier to obtain? 2y (you only have to multiply the bottom equation by 2) Step 2: Determine which variable to eliminate.

6
**Example 1 Cont… 2x + 2y = 6 3x – y = 5 x = 2 2(2) + 2y = 6 4 + 2y = 6**

Multiply the bottom equation by 2 2x + 2y = 6 (2)(3x – y = 5) 8x = 16 x = 2 2x + 2y = 6 (+) 6x – 2y = 10 Step 3: Multiply the equations and solve. 2(2) + 2y = 6 4 + 2y = 6 2y = 2 y = 1 Step 4: Plug back in to find the other variable.

7
Example 1 Cont… 2x + 2y = 6 3x – y = 5 (2, 1) 2(2) + 2(1) = 6 3(2) - (1) = 5 Step 5: Check your solution. Solving with multiplication adds one more step to the elimination process.

8
Example 2 x + 4y = 7 4x – 3y = 9 Step 1: Put the equations in Standard Form. They already are! Find the least common multiple of each variable. LCM = 4x, LCM = 12y Which is easier to obtain? 4x (you only have to multiply the top equation by -4 to make them inverses) Step 2: Determine which variable to eliminate.

9
**Example 2 Cont… x + 4y = 7 4x – 3y = 9 y = 1 x + 4(1) = 7 x + 4 = 7**

Multiply the top equation by -4 (-4)(x + 4y = 7) 4x – 3y = 9) y = 1 -4x – 16y = -28 (+) 4x – 3y = 9 Step 3: Multiply the equations and solve. -19y = -19 x + 4(1) = 7 x + 4 = 7 x = 3 Step 4: Plug back in to find the other variable.

10
**Example 2 Cont… x + 4y = 7 4x – 3y = 9 (3, 1) (3) + 4(1) = 7**

4(3) - 3(1) = 9 Step 5: Check your solution.

11
**Once the equations are in standard form, what should you do first when solving with elimination?**

Add or subtract the equations. Multiply the equations. Plug numbers into the equation. Solve for a variable. Check your answer. Determine which variable to eliminate. Put the equations in standard form.

12
**Which variable is easier to eliminate?**

3x + y = 4 4x + 4y = 6 x y 6 4 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32

13
Example 3 3x + 4y = -1 4x – 3y = 7 Step 1: Put the equations in Standard Form. They already are! Find the least common multiple of each variable. LCM = 12x, LCM = 12y Which is easier to obtain? Either! I’ll pick y because the signs are already opposite. Step 2: Determine which variable to eliminate.

14
**Example 3 Cont…. 3x + 4y = -1 4x – 3y = 7 x = 1 3(1) + 4y = -1**

Multiply both equations (3)(3x + 4y = -1) (4)(4x – 3y = 7) x = 1 9x + 12y = -3 (+) 16x – 12y = 28 Step 3: Multiply the equations and solve. 25x = 25 3(1) + 4y = -1 3 + 4y = -1 4y = -4 y = -1 Step 4: Plug back in to find the other variable.

15
**Example 3 Cont…. 3x + 4y = -1 4x – 3y = 7 (1, -1) 3(1) + 4(-1) = -1**

4(1) - 3(-1) = 7 Step 5: Check your solution.

16
**What is the best number to multiply the top equation by to eliminate the x’s?**

3x + y = 4 6x + 4y = 6 -4 -2 2 4 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32

17
**You Try! Solve using elimination**

2x – 3y = 1 x + 2y = -3 (2, 1) (1, -2) (5, 3) (-1, -1)

18
**Find two numbers whose sum is 18 and whose difference 22.**

19
Homework Problems: Odd Only

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google